A dozen dozens - Ziefert Harriet; Demarest Chris L (New York, NY, USA : Viking, 1998)
Illustrations and rhyming text present dozens--or half-dozens--of pigs, tulips, apples, eggs, socks, babies, and more. Includes related activities.